Kyrgyz Republic : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2013)
The government of the Kyrgyz Republic is determined to consolidate its finances over the coming years. This note describes the main elements of the tax regime in the Kyrgyz Republic, looks into tax incentives, and provides some reform options to raise revenues. The second note is on monetary policy in the Kyrgyz Republic, which faces challenges with respect to formulation and efficacy given the low monetization, the shallow financial system, high dollarization, and a predominantly cash-based economy.